Guidance Note on the Assessment of Reserve Adequacy and Related Considerations. (Policy Papers; Policy Paper, 2016)
operational guidance to staff on reserve adequacy discussions in the IMF's bilateral and multilateral surveillance. It is based on the views presented in the policy paper Assessing Reserve Adequacy-Specific Proposals and the related Board discussion. The note addresses key issues related to Staff's advice on the assessment of the adequacy of reserves and related items, including answering the following questions: What is the expected coverage of reserve issues at different stages of the bilateral surveillance process (Policy Note, mission, and Staff Report)? Which reserve adequacy tools best fit different economies based on their financial maturity, economic flexibility, and market access? What do possible reserve needs in mature markets relate to, and how can their adequacy be assessed? How can reserve adequacy discussions for emerging and deepening financial markets be tailored and applied to better evaluate reserve levels in: (i) commodity-intensive economies; (ii) countries with capital flow management measures (CFMs); and (iii) partially and fully dollarized economies? What reserve adequacy considerations hold for countries with limited access to capital markets? How can metrics for these economies be tailored to evaluate their reserve needs? How should potential drains on reserves be covered? What are the various measures of the cost of reserves for countries with and without market access?